HUBUNGAN PERAWATAN VULVA HYGIENE PADA WANITA USIA SUBUR DENGAN KEJADIAN FLOUR ALBUS DI DESA MATTIROWALIE KECAMATAN TANETE RIAJA KABUPATEN BARRU - St. Hasriani; Wilda Rezki Pratiwi; Asnuddin Asnuddin; Meriem Meisyaroh Syamson; Fitriana Bunyanis (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2023)
Physical changes in the reproductive organs of women of childbearing age are influenced by the maturation of sexual hormones. An increase in the hormones estrogen and progesterone causes secondary sex changes including changes in body posture, breast enlargement, genital and axillary hair growth and menstruation begins. The aim of this study was to determine the relationship between vulva hygiene care in women of childbearing age and the incidence of flour albus in Mattirowalie Village. Tanete Riaja District, Barru Regency. This type of research is an observational method with a Cross Sectional Study approach. The population is all women of childbearing age who are in Mattirowalie Village, Tanete Riaja District, Barru Regency, totaling 1,041 people. The sample was 91 women of childbearing age in Mattirowalie Village, Tanete Riaja District, Barru Regency, using a purposive sampling technique. The results showed that of the 91 people sampled, 13 people (14.3%) had poor vulva hygiene and 78 people (85.7%) had good vulva hygiene. The results showed that of the 91 people who were sampled, 14 people (15.4%) had abnormal flour albus and 77 people (84.6%) had normal flour albus. The results showed that there was a significant relationship between vulva hygiene care in women of childbearing age and the incidence of flour albus in Mattirowalie Village, Tanete Riaja District, Barru Regency.